#TripleNegativeBreastCancer on Instagram. (October 2021) - Henderson, Alesha; Miller, Carrie A.; Sutton, Arnethea L.; Guidry, Jeanine P. D.
Little is known about how triple negative breast cancer (TNBC) is discussed on the visual social media platform, Instagram. A greater understanding of the experiences of TNBC survivors that are documented on this platform may inform us of how this group of survivors cope with this rare, but aggressive form of breast cancer. This study analyzed a random sample ( N = 501) of Instagram posts using the hashtag #triplenegativebreastcancer. Using a quantitative content analysis, posts were coded for the presence of health belief model constructs as well as the presence of treatment-related experiences, social support, and hereditary breast cancer genetic mutations (BRCA 1/2). Our findings suggest that health organizations and agencies are not utilizing Instagram as a conduit of health communications about TNBC to reach individuals worldwide. This article provides insights into potential strategies that can be used by these entities to promote user engagement with posts about TNBC, such as utilizing health messaging that is episodic in nature, uses supportive and encouraging words, and provides information about chemotherapy.